Literary Works as Literary Learning Media Oriented to the Concept of Multiculturalism Education: A Study of Indonesian Metro Pop Novels - Zulfadhli Zulfadhli; Hasanuddin WS; Syahrul Ramadhan (STAI Hubbulwathan Duri, 2023)
The introduction of multiculturalism values can be applied through education. One of the models offered is utilising literary works as a medium for instilling the values of multiculturalism education. This study explains how literary works, particularly Indonesian metro pop novels, can be used as literary learning media oriented to multiculturalism education. The method in this study is literary research. Literary research aims to reveal various phenomena by making literary works as research objects. The literary works used as sources of research data in this study were eight Indonesian metropop novels published in the 2000-2020 period, which were selected using a purposive sampling technique. The data were collected using reading and note-taking techniques. Data were analyzed by content analysis method. The study results show that the diversity of culture, ethnicity, language, religion, race, ethnicity, gender, socio-economic class, customs and social traditions in Indonesia places multicultural education as essential. Educational efforts with a multicultural perspective are very necessary to avoid social conflicts because of diversity.